Effects of environmental air pollutants on CFTR expression and function in human airway epithelial cells. (December 2021) - Nguyen, Jenny P.; Huff, Ryan D.; Cao, Quynh T.; Tiessen, Nicholas; Carlsten, Christopher; Hirota, Jeremy A.
Abstract: The airway epithelium is exposed to a variety of air pollutants, which have been associated with the onset and worsening of respiratory diseases. These air pollutants can vary depending on their composition and associated chemicals, leading to different molecular interactions and biological effects. Mucociliary clearance is an important host defense mechanism against environmental air pollutants and this process is regulated by various ion transporters including the cystic fibrosis transmembrane conductance regulator (CFTR). With evidence suggesting that environmental air pollutants can lead to acquired CFTR dysfunction, it may be possible to leverage therapeutic approaches used in cystic fibrosis (CF) management. The aim of our study was to test whether environmental air pollutants tobacco smoke extract, urban particulate matter, and diesel exhaust particles lead to acquired CFTR dysfunction and whether it could be rescued with pharmacological interventions. Human airway epithelial cells (Calu-3) were exposed to air pollutant extracts for 24 h, with and without pharmacological interventions, with readouts of CFTR expression and function. We demonstrate that both tobacco smoke extract and diesel exhaust particles led to acquired CFTR dysfunction and that rescue of acquired CFTR dysfunction is possible with pharmacological interventions in diesel exhaust particle models. Our study emphasizes that CFTR function is not only important in the context of CF but may also play a role in other respiratory diseases impacted by environmental air pollutants. In addition, the pharmacological interventions approved for CF management may be more broadly leveraged for chronic respiratory disease management. Graphical abstract: Unlabelled Image Highlights: Tobacco smoke extract and diesel exhaust particles result in acquired CFTR dysfunction. VX-770 and ascorbic acid rescue acquired CFTR dysfunction. Oxidative stress and a reduction in CFTR expression contribute to CFTR dysfunction. Collectively, our data suggests that air pollutants can lead to acquired CFTR dysfunction and emphasizes the importance of CFTR function beyond CF. Our findings also suggest that current therapeutics used in CF management could have broad applications and potentially benefit healthy individuals, and those with respiratory diseases, who are exposed to poor air quality.